Interpretowanie i konstruowanie swojej dorosłości z perspektywy osób niepełnosprawnych - Myśliwczyk, Iwona; Ćwirynkało, Katarzyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Research on the adulthood of people with disabilities is still scarce. In the article the results of a qualitative research project involving the use of three individual, indepth semistructured interviews and a narrative analysis approach are presented. The authors show the everyday life of adults with disabilities, which is not thrown into the scheme, because it distances itself from stereotypes. Positive self-perception of these people – depicted in narratives – is visible in their perception of adulthood, which is implemented in the same way as in the case of the able-bodied, so that’s the adulthood with prospects of self-realization. Difficulties implied by disability become insignificant.